A customer-oriented manager for B2B services - e uthor (London, UK : ISTE, Ltd. ; Hoboken, NJ : Wiley, 2022)
The notion of customer orientation is becoming a necessity rather than a choice for many companies. It is a lasting response to competitive pressure and supports the company in a renewed definition of its mission, beyond direct economic gain. Within B2B services, the manager, through proximity to their team, their market and their client, is the essential actor in the deployment of this orientation. A Customer-oriented Manager for B2B Services provides managers with the knowledge and tools necessary to implement customer orientation themselves, with the involvement of their extended team. To this end, this book presents a four-step approach: understand the fundamentals of customer orientation in B2B services, know the customer, make the most of the offer and deliver the service.
Understanding the Fundamentals of Customer Orientation in B2B Services. Understanding the Fundamentals of Customer Orientation in B2B Services -- Customer Orientation -- Reality and Challenges of Service -- Markers of B2B -- Knowing the Customer. Knowing the Customer -- Modeling the Industrial Sector -- Understanding the Purchase -- Identifying Service Targets -- Making the Most of the Offer. Making the Most of the Offer -- Acting Against the Risk of Commoditization -- Formalizing Your Offer -- Taking Care of One Commercial Action -- Delivering the Service. Delivering the Service -- Unlocking Human Potential -- Managing Service Operations -- Marketing the Tangibles -- Conclusion -- References -- Index -- Other titles from iSTE in Innovation, Entrepreneurship and Management
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed March 29, 2022).
John Wiley and Sons
Keywords: Industrial marketing -- Management; Marketing industriel -- Gestion; Industrial marketing -- Management